A SYNTACTIC ANALYSIS OF NOUN PHRASE FOUND IN JUSTIN BIEBER S SONG LYRICS PURPOSE ALBUM - Manisde Laia (Research on English Language Education, 2023)
This research was aimed at analyzing the structures and functions of noun phrase which have been used in Justin Bierbers song that contained in purposealbum.This research was designed by using qualitative method. The data were analyzed byusing Creswelltheory. There are data condensation, data display, and drawing conclution. The result of data analysis showed that there were 148 noun phrases which have been found. They were classified into 6 structures:determiner+head,determiner+pre-modifier+head, determiner+head+postmodifier,determiner+premodifier+head+postmodifier,head+modifier,andpremodifier+head. In addition, there are six syntactic functions: as subject, subject of completment, object, object of preposition, object of completment and component of preposition. Based on the research finding, it can be concluded that mostly song lyrics in purpose album were intended to use noun phrase to construct the sentences and delivering meaning of the song lyrics. Thus, noun phrase is the effective aspect that can be used in aliterary works to provide or give information in detail about a sentence depended on the function attached to the noun phrase.